Hemogram parameters for predicting pulmonary embolism in patients with deep venous thrombosis - Kaya H; Kurt R (Dove Medical Press, 2015)
Hakki Kaya, Recep KurtDepartment of Cardiology, Cumhuriyet University Medical School, Sivas, TurkeyWe read the article of Sevuk et al,1 published in the August 2015 issue of your journal, with great interest. The authors concluded that percentage change in serial measurements of mean platelet volume (MPV) and platelet-distribution width (PDW) is valuable in predicting the development of pulmonary thromboembolism in patients with a previous history of deep venous thrombosis (DVT). In a similar study conducted by Braekkan et al2 (Tromsø Study), MPV on admission was shown to predict pulmonary thromboembolism.  Read the original paper here